Factors influencing the popularity of accounting at Malaysian higher school certificate - Ibrahim Mohd Yusoff, Tamby Chek Ibrahim, Ismail Khalid, (Universiti Pendidikan Sultan Idris, 2003)
Factors influencing the popularity of accounting at Malaysian higher school certificate by Ibrahim Mohd Yusoff, Tamby Chek Ibrahim, Ismail Khalid,